How do emigrants perceive changes in their L1: influence of sociolinguistic factors - Vilkienė, Loreta (Taikomoji kalbotyra, 2017)
The paper aims at providing insights into sociolinguistic factors which affect the understanding of the first-generation emigrants that their L1 is different (or not) from Lithuanian used in Lithuania. The data for the analysis comes from the project The Language of Emigrants (2011-2013, coordinator Meilutė Ramonienė, funded by The State Commission of the Lithuanian Language). The data from the surveys were analysed using SPSS (version 20). Answers to the target questions of 1,491 first-generation emigrants were analysed. As the assumption was that the perception of change in one’s L1 can be a reflection of the L1 attrition of that individual, seven factors that could play a role in this change based on the previous studies were chosen for the analysis. The analysis revealed that five factors played a role in the perception of change of one’s L1:1. The length of the stay abroad: the longer the respondents lived abroad, the higher percentage of the respondents claimed that their L1 was different from the Lithuanian language used in Lithuania.2. The age of the respondents: older respondents more frequently thought that their L1 had changed.3. Gender: fewer men perceived their L1 as different. Also, the interplay between gender and occupation was important.4. Contact with the L1 in the country of residence: the general use of L1 in the country of residence played a role in the perceptions, especially the use of L1 at home.5. Ethnic identity: respondents who strongly identified themselves as Lithuanians perceived the difference of their language.The answer to the question which factors were the most important for perceiving the change in one’s L1 can be informative for answering the question what influences a faster or slower loss of L1 when living in emigration; however, to answer this question, analysis of actual language performance of the emigrants would be necessary.It has to be acknowledged that some of the analysed subgroups were rather small; therefore, insights about them should be tested on a larger number of respondents. Also, a limitation of this study is the fact that during the project The Language of Emigrants, emigrants who intentionally had cut the ties with Lithuania were not contacted; therefore, the data does not reflect their attitudes and their perception about their language change. It has to be noted that all the insights only concern the respondents of the participants in The Language of Emigrants project.
Keywords: first-generation emigrants; native language (L1); perception of changes in L1; language attrition; sociolinguistic factor; quantitative data